A Novel hepatocellular carcinoma specific hypoxic related signature for predicting prognosis and therapeutic responses - Cai, Guangzhen; Zhu, Jinghan; Ning, Deng; Li, Ganxun; Zhang, Yuxin; Xiong, Yixiao; Liang, Junnan; Yu, Chengpeng; Chen, Xiaoping; Liang, Huifang; Ding, Zeyang (Frontiers in Immunology, 2022)
Hypoxia is an important feature of the tumor microenvironment(TME) and is closely associated with cancer metastasis, immune evasion, and drug resistance. However, the precise role of hypoxia in hepatocellular carcinoma(HCC), as well as its influence on the TME, and drug sensitivity remains unclear. We found the excellent survival prediction value of the Hypoxia_DEGs_Score model. In hypoxic HCC, somatic mutation, copy number variation, and DNA methylation were closely related to hypoxic changes and affected tumorigenesis, progression, metastasis, and drug resistance. In HCC, aggravated hypoxic stress was found to be accompanied by an immune exclusion phenotype and increased infiltration of immunosuppressive cells. In the validation cohort, patients with high Hypoxia_DEGs_Score were found to have worse immunotherapeutic outcomes and prognoses, and may benefit from drugs against cell cycle signaling pathways rather than those inhibiting the PI3K/mTOR pathway. Hypoxia_DEGs_Score has an excellent predictive capability of changes in the TME, the efficacy of immunotherapy, and the response of drugs. Therefore, Hypoxia_DEGs_Score can help develop personalized immunotherapy regimens and improve the prognosis of HCC patients.